Associations among animal, carcass, muscle characteristics, and fresh meat color traits in Charolais cattle. (June 2018) - Gagaoua, Mohammed; Picard, Brigitte; Monteils, Valérie
Abstract: This study investigated the effects of animal, carcass and muscle characteristics on initial color traits of steaks from 887 Charolais cattle. First, the fixed factors of year of birth, experiment and sex had strong impacts on color traits. From the covariates, increased age lead to intense color (low h*, −1.55 units) and darker and vivid meat (high a*, b* and C* : +4.56, +3.41 and +5.61, respectively). Increases in fatness score and carcass fat weight were associated with increases in a*, b* and C* (redness; +2.90 to +4.06 for a* ; yellowness; +2.60 to +3.76 for b* ; and vividness, +3.87 to +5.49 for C* ) and a darker colored lean ( L* ; −1.56 to −3.23). As pH24h increased, a* (less red) and C* (less vivid) decreased (−3.06), whereas hue angle increased (+2.69) leading to poorer color. The selection of animals for high degree of muscularity or slaughter weight resulted in lighter and darker meat, respectively. The studied covariates could be used as indicators of Charolais beef color traits. Highlights: Ultimate pH was >5.8 for 1.8% of cattle, and affected a*, C* and h* traits. Increased age lead to intense color (low h*, −1.55 units) and darker and vivid meat. Fatness score and carcass fat weight are precursors of red and vivid Charolais beef. High degree of muscularity or slaughter weight, lead to lighter and darker meat, respectively Principal component regression (PCR), a promising tool for the prediction of beef color traits.